Placental pathological findings and their association with maternal and fetal clinical outcomes: A cross-sectional study - Soheila Sarmadi; Elham Mirzaian; Fatemeh Nili; Fatemeh Khalafrezaei (International Journal of Reproductive BioMedicine)
Background: Placental pathological changes can occur in both normal and high-risk pregnancies, leading to adverse maternal and neonatal outcomes.